2012
DOI: 10.1007/s10571-012-9825-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Spinal Cord Injury Induces Genetic Damage in Multiple Organs of Rats

Abstract: Spinal cord injury (SCI) is a devastating condition with important functional and psychological consequences. However, the underlying mechanisms by which these alterations occur are still not fully understood. The aim of this study was to analyze genomic instability in multiple organs in the acute phase of SCI by means of single cell gel (comet) assay. Rats were randomly distributed into two groups (n = 5): a SHAM and a SCI group killed 24 h after cord transection surgery. The results pointed out genetic damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Interestingly, Medalha et al . have demonstrated that acute DNA damage extends beyond the spinal cord in SCI rats to affect blood, liver, and the kidneys using the comet assay to detect DNA strand breaks (Medalha et al, 2012). …”
Section: Evidence For Dna Damage In Acute Cns Injuries and Neurodegenmentioning
confidence: 99%
“…Interestingly, Medalha et al . have demonstrated that acute DNA damage extends beyond the spinal cord in SCI rats to affect blood, liver, and the kidneys using the comet assay to detect DNA strand breaks (Medalha et al, 2012). …”
Section: Evidence For Dna Damage In Acute Cns Injuries and Neurodegenmentioning
confidence: 99%
“…Dagci et al 2009a found DNA strand breaks in the brain and kidney of SCI rats [ 53 ]. Consistently, Medalha et al showed DNA strand breaks in the liver and kidney [ 77 ], and Sakarcan et al similarly reported oxidative DNA damage (i.e., 8-oxodG) in the kidney [ 34 ]. The brain is directly connected to the spinal cord, and similar effects as in the spinal cord might be predicted.…”
Section: Oxidative Dna Damage Is Understudied After Scimentioning
confidence: 78%
“…Using HPLC, Ozgonul et al found DNA damage biomarkers (i.e., 5-(hydroxymethyl) uracil (5HMU) and 2′-deoxyuridine (2dU)) in the urine at sub-acute time points (7 dpi) and early chronic time points (28 dpi) [ 55 ]. In addition, Medalha et al showed DNA strand breaks using the comet assay in the blood of SCI rats at 1 dpi [ 77 ]. These findings indicate that factors produced at the injury site can traverse the disrupted blood–brain barrier and may have systemic effects.…”
Section: Oxidative Dna Damage Is Understudied After Scimentioning
confidence: 99%
“…In the present study, the plasma nDNA level on day 14 was independently associated with outcome, suggesting that the therapeutic window is within the first 14 days after injury. Medalha et al [49] demonstrated that acute DNA damage extends beyond the spinal cord in SCI rats to affect the blood, liver, and kidneys. Bao et al [50] administrated a monoclonal antibody against CD11d integrin, an integral leukocyte adhesion protein that reduces oxidative stress-related DNA oxidation after severe compression injury.…”
Section: Discussionmentioning
confidence: 99%